PENERJEMAHAN PEGON DALAM KITAB KUNING PESANTREN - R. Ahmad Nur Kholis; Ahsanul (LP3M IAI Al-Qolam, 2022)
This study aims at explaining the writing technics and principals as well as the translation of “pegon” script in “kitab kuning” as it is applied in the tradition of “pesantren”. It concludes the following points. First, the writing technique of “pegon” script is based on the vowels used in Malay and Javanese language which is assimilated to the writing technique of the Arabic language. Second, any signs showing the indicator of syntactic parsing are written above the main text (superscript). Third, any signs showing the lexical access are written below the main text (subscript). Fourth, any dependant word particle (huruf) is not given any sign, so it should be memorized. Fifth, any signs of reference are written following the rule of similarity between the sign on the reference and the referred word. These latter signs are written following these rules: (1) any signs for the reference are written below the main text (subscript), and any signs for the referred word are written above the main text (superscript), (2) any signs of reference that refers to any words, phrase, or sentence located too far from the reference are written by using a kind of footnote